Changes in intestinal barrier function and gut microbiota in high-fat diet-fed rats are dynamic and region dependent - Hamilton, M. Kristina; Boudry, Gaëlle; Lemay, Danielle G.; Raybould, Helen E. (American journal of physiology: Gastrointestinal and liver physiology, 2015)
A causal relationship between the pathophysiological changes in the gut epithelium and altered gut microbiota with the onset of obesity have been suggested but not defined. The aim of this study was to determine the temporal relationship between impaired intestinal barrier function and microbial dysbiosis in the small and large intestine in rodent high-fat (HF) diet-induced obesity. Rats were fed HF diet (45% fat) or normal chow (C, 10% fat) for 1, 3, or 6 wk; food intake, body weight, and adiposity were measured. Barrier function ex vivo using FITC-labeled dextran (4,000 Da, FD-4) and horseradish peroxidase (HRP) probes in Ussing chambers, gene expression, and gut microbial communities was assessed. After 1 wk, there was an immediate but reversible increase in paracellular permeability, decrease in IL-10 expression, and decrease in abundance of genera within the class Clostridia in the ileum. In the large intestine, HRP flux and abundance of genera within the order Bacteroidales increased with time on the HF diet and correlated with the onset of increased body weight and adiposity. The data show immediate insults in the ileum in response to ingestion of a HF diet, which were rapidly restored and preceded increased passage of large molecules across the large intestinal epithelium. This study provides an understanding of microbiota dysbiosis and gut pathophysiology in diet-induced obesity and has identified IL-10 and Oscillospira in the ileum and transcellular flux in the large intestine as potential early impairments in the gut that might lead to obesity and metabolic disorders.